Digital transformation and AI in Moroccan cities: Pathways to smart urban governance - Ghaleb, Najoua El Abbas El; Cherti, Anass; Jouiet, Insaf; Kharbach, Mohamed; Laghzaoui, Fadoua (Edelweiss Applied Science and Technology, 2025)
The pervasive influence of digital transformation and artificial intelligence (AI) is fundamentally reshaping urban management paradigms. These technologies offer novel approaches to improving public service efficiency, enhancing data accessibility, fostering citizen participation, and bolstering urban resilience. This research investigates the specific impacts of these technological advancements on the governance of Moroccan cities. Employing structural equation modeling (SEM) with data gathered from 320 respondents within the Tanger-Tétouan-Al Hoceïma region, we empirically assess these relationships. The analysis reveals a substantial positive association between digital transformation and both public service efficiency (β = 0.60, p < 0.01) and data accessibility (β = 0.55, p < 0.01). Similarly, AI adoption demonstrates a significant contribution to urban resilience (β = 0.50, p < 0.01) and the optimization of urban infrastructure management. However, the influence of AI on citizen engagement appears comparatively modest (β = 0.20, p < 0.05), suggesting a critical need for complementary strategies focused on digital inclusion and public awareness. While technological progress is evident, persistent challenges remain, including suboptimal inter-institutional coordination, persistent digital divides, and limitations in the availability of real-time, open data. To realize the full potential of digital transformation, public policies should prioritize information system interoperability, transparency in municipal decision-making processes, and the active involvement of citizens in urban governance. This study provides empirical insights into the evolving landscape of smart cities in Morocco, underscoring the necessity of an integrated, holistic approach to maximize the benefits of digital technologies in urban administration. Future scholarly inquiry could profitably examine the longitudinal evolution of these impacts and conduct comparative analyses of the performance of diverse Moroccan cities in the context of smart city development.